Synthesin and Characterization Chitosan Film with Silver Nanoparticle Addition As A Multiresistant Antibacteria Material - Endang Susilowati; Sri Retno Dwi Ariani; Lina Mahardiani; Luthfia Izzati (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2021)
The synthesis of chitosan films with the addition of silver nanoparticles (AgNps) has been carried out in 2 stages. The first stage is to make colloidal silver nanoparticles with chitosan as a stabilizer and a reducing agent with NaOH as an accelerator and assisted by microwave irradiation. The second stage is to make a film from colloidal silver nanoparticles-chitosan by casting method. The formation of silver nanoparticles was identified using a UV-Vis spectrophotometer and TEM. Chitosan films with the addition of AgNps were characterized by chemical, physical and mechanical properties. Furthermore, the antibacterial activity was tested against multi-resistant bacteria ESBL and MRSA. The results showed that the formation of AgNps was indicated by the appearance of an absorption band at 400-413 nm with a size of less than 6 nm. The FTIR spectra showed that there was a slight shift at the 1604 cm-1 peak which indicated that the AgNps interacted with the NH2 group on D-glucosamine of chitosan. The films morphology with addition Ag NPs tends to be rough in surface and cross-sectional. The presence of AgNps tends to increase the swelling value, tensile strength and film elasticity. Chitosan film with the addition of silver nanoparticles has antibacterial activity against multi-resistant bacteria ESBL and MRSA. The anti-bacterial activity of the film was derived solely from the silver nanoparticles.